PERENCANAAN PAKET WISATA TRACKING DESA TENGANAN KECAMATAN MANGGIS KABUPATEN KARANGASEM-BALI - Padmi Triyanti, Ni Nyoman; Suwena, I Ketut; Sudana, I Putu (Jurnal IPTA (Industri Perjalanan Wisata), 2015)
Tenganan village of Karangasem regency is one of the ancient Balinese village. Tenganan village has the potential to be used as a variety of attractions both natural and cultural potential. One is the tourist tracking. Given that there are many potential Tenganan village that can be used as a tracking tour, but have not got a touch of communities and local governments. Lack of promotion and accessibility is one obstacle why several other attractions have not been able to flourish. In this regard, the issues raised are (1) what potential there is in Karangasem regency which is used as a tracking tour? (2) How to plan a tour package tracking can be developed to support the potential in Tenganan village? As for who becomes goals of this research was to determine the potential for tracking in the Tenganan Village, and how to plan a tour package tracking to support the potential of Tenganan village. Data collection in this research was done by observation, interviews, documentation and library research. Type of data used is the qualitative data supported by quantitative data, while the data source is the primary data and secondary data. Results of the research showed that of the observations conducted of the potential tracking in Tenganan village is still a lot of potential that has not been developed and the maximum attention, especially from the local government. Development of tourism in the village of Tenganan just focus on gringsing fabric crafts and architecture of ancient houses, so that promotion to tourists to attractions alternative needs to be improved.
Keywords: Tourism Tracking, Potentials, Plan a Tour Package